1991
DOI: 10.1007/bf01402512
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation and cerebral haemodynamics

Abstract: An increase of regional cerebral blood flow (rCBF) has been shown to occur in man during spinal cord stimulation (SCS) by Hosobuchi (1986) and by Meglio et al. (1988) using the 133-Xenon wash-out technique. In this paper we report the effects of SCS on CBF as measured by two different techniques: 8 patients were studied with the 133-Xe method and 28 with the transcranial doppler sonography (TCD), in two cases both studies were performed. The aim of our study was to: 1-verify the effect of SCS on CBF, 2-compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
7
28
0
Order By: Relevance
“…After the first observation published by Hosobuchi of an increase in CBF during cervical SCS in man [6], we confirmed his clinical report by utilizing the same 133 Xe inhalation technique and using transcranial Doppler sonography [7,8]. Subsequently experimental data concerning SCS induced CBF changes in animals were studied by Garcia-March, our group and Isono by means of electromagnetic flowmetry, Doppler sonography and hydrogen clearance method.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…After the first observation published by Hosobuchi of an increase in CBF during cervical SCS in man [6], we confirmed his clinical report by utilizing the same 133 Xe inhalation technique and using transcranial Doppler sonography [7,8]. Subsequently experimental data concerning SCS induced CBF changes in animals were studied by Garcia-March, our group and Isono by means of electromagnetic flowmetry, Doppler sonography and hydrogen clearance method.…”
Section: Discussionsupporting
confidence: 57%
“…Spinal cord stimulation (SCS) interferes with the mechanisms of regulation of the cardiovascular and cerebro-vascular systems [1][2][3]. After demonstrating that SCS increases cerebral blood flow (CBF) in man and in animals we have shown a preventing effect of SCS on experimental 'early spasm' in the rabbit [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hosobuchi (1985) was the first to report that cervical SCS (cSCS) produced an increase in cerebral blood flow (CBF) in humans. Subsequent clinical observations demonstrated that cSCS decreases cerebral vascular resistance and increases blood flow velocity, leading to an enhancement of the local-regional delivery of oxygen Mazzone et al 1996;Meglio et al, 1991a, b). Therefore, the promising results of SCSinduced CBF augmentation have led some clinicians to use this procedure to treat various cerebral vascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the promising results of SCSinduced CBF augmentation have led some clinicians to use this procedure to treat various cerebral vascular disorders. These cerebral diseases and/or pathological conditions include cerebral ischemia (Broseta et al, 1994;De Andres et al, 2007;Hosobuchi, 1991), ischemic spastic hemiparesis (Visocchi et al, 1994), focal cerebral ischemia (Meglio et al, 1991a, b;Ebel et al, 2001;Sagher et al, 2003;Sagher and Huang 2006;Robaina et al, 2004), cerebral vasospasm Karadag et al, 2005;Visocchi et al, 2001), stroke (Hosobuchi, 1991;Matsui and Hosobuchi, 1989;Visocchi et al, 1994Visocchi et al, , 2001, ischemic cerebral oedema (Gonzalez-Darder and Canadas-Rodriguez, 1991), postapoplectic spastic hemiplegia (Nakamura and Tsubokawa, 1985), prolonged coma (Fujii et al, 1998), persistent vegetative state (Funahashi et al 1989;Kanno et al, 1987;Kuwata, 1993), as well as migraine and posttraumatic cervicogenic headache (Dario et al, 2005). However, the underlying mechanisms of blood flow improvement are not well understood ).…”
Section: Introductionmentioning
confidence: 99%
“…SCS has been shown to augment CBF and speculated to protect the brain from focal ischemia in a large series of experiments, both on animals and on humans [47,48,49,50,51,52,53], and has been proposed for the treatment of several cerebral low-perfusion syndromes [54,55,56,57,58,59,60,61,62,63,64,65,66,67]. However, there is not yet an ultimate scientific explanation; moreover, a clear understanding of the mechanisms elicited by SCS is still lacking [4,53,68].…”
Section: Discussionmentioning
confidence: 99%